Law and Ecology New Environmental Foundations - Philippopoulos-Mihalopoulos, Andreas (2011)
Law and Ecology: New Environmental Foundations contains a series of theoretical and applied perspectives on the connection between law and ecology, which together offer a radical and socially responsive foundation for environmental law. While its legal corpus grows daily, environmental law has not enjoyed the kind of jurisprudential underpinning generally found in other branches of law. This book forges a new ecological jurisprudential foundation for environmental law - where 'ecological' is understood both in the narrow sense of a more ecosystemic perspective on law, and in the broad sense of critical self-reflection of the mechanisms of environmental law as they operate in a context where boundaries between the human and the non-human are collapsing, and where the traditional distinction between ecocentrism and anthropocentrism is recast. Addressing current debates, including the intellectual property of bioresources; the protection of biodiversity in view of tribal land demands; the ethics of genetically modified organisms; the redefinition of the 'human' through feminist and technological research; the spatial/geographical boundaries of environmental jurisdiction; and the postcolonial geographies of pollution - Law and Ecology redefines the way environmental law is perceived, theorised and applied. It also constitutes a radical challenge to the traditionally human-centred frameworks and concerns of legal theory.